Características dinâmicas e termodinâmicas dos vórtices ciclônicos de altos níveis no Nordeste do Brasil - Reis, Jean Souza dos (Brasil, 2018)
The objective of this work was to study the dynamic and thermodynamic characteristics of the High Level Cyclonic Vortexes (HLCV) in the Northeast of Brazil (NEB) using an objective HLCV identification algorithm (OHIA) using ERA-Interim data from the model reanalysis European Center for Medium-Range Weather Forecasts (ECMWF), and the Precipitation Impact Assessment (NCEP), the Climate Prediction Center (CPC) of the National Centers for Environmental Prediction (NCEP) in the period from 1980 to 2016. The OHIA presented efficiency gain after the two improvements added (SVAV method and four new quadrants of the wind turning) and could be redirected to other studies. The OHIA results were confirmed by the climatology itself, identifying 1493 HLCV, 51% occurring in summer, 23% in autumn, 5% in winter and 21% in austral spring. In the analysis of the spatial climatology of HLCV occurrence, the regions with the greatest impact of this system on the continent were: The central region of Pernambuco; The coast in the border of Pernambuco and Paraíba; northern coast of Bahia; Central region of Bahia; South region of Bahia. It was observed that in the South Atlantic Ocean adjacent to the coast of NEB there is a large density of HLCV. In the summer, HLCV occur more frequently in the coastal and south-central regions of Bahia, central Pernambuco and along the coast of the Pernambuco and Paraíba counties, while in the autumn the central and coastal regions of Bahia are most affected. Also, an evidence that this system acts as an inhibitor of precipitation in NEB has been shown when precipitation and preferential positioning of the HLCV is related. This result indicates that in addition to the systems that alter the dynamics of precipitation, the HLCV is responsible for the water deficit. The atmospheric profile of the divergence showed that there is a phase change in the mean atmosphere. The monthly analysis of vorticity and divergence showed that March is the month of HLCV more intense. Two conceptual soundings were made from ...